Monitoring and Conservation Education of Javan Endemic Dragonflies Genus Drepanosticta in Petungkriyono Forest (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Endemic dragonflies of the genus Drepanosticta in Java play a crucial role as bioindicators of aquatic environmental quality in tropical rainforest ecosystems. However, increasing land-use change in Petungkriyono Forest poses a significant threat to their survival. This study aimed to disseminate scientific information on the abundance and distribution of Drepanosticta species and to implement conservation education programs targeting elementary school students and local communities. Abundance and distribution data were collected from four sites using line transect surveys and direct count methods. The survey recorded three species, namely Drepanosticta gazella, Drepanosticta spatulifera, and Drepanosticta sundana, with D. spatulifera being the most dominant across all sites. Conservation education activities involved 27 students from SD Negeri 02 Tlogopakis through interactive lectures, educational animated videos, and direct field observations to enhance their understanding of dragonfly ecology and conservation. Furthermore, public outreach was conducted on 7 June 2021 through the distribution of infographic posters containing information on Javan endemic dragonflies and their ecological importance to local residents. This integrated approach of scientific dissemination and community-based conservation education is expected to increase environmental awareness and foster active participation in biodiversity conservation efforts in Petungkriyono Forest.